The frontiers of human rights - Bhuta, Nehal, 1975- (Oxford : Oxford University Press, 2016)
Grappling with the promise and the dilemmas of the extraterritorial application of human rights law, this volume investigates the legal, theoretical, and practical questions raised by extending states' human rights obligations beyond their national territories.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 17, 2016).
Keywords: Human rights; International law and human rights; Law; International law